Gemstones : a concise reference guide - Hansen, Robin (Princeton University Press, 2022)
"Gemstones have been a source of delight and fascination for thousands of years, from the icy brilliance of diamond and the soft iridescence of pearl to tough jade gems once used in weapons and pink topaz that was popular in Victorian jewelry. This book covers every known type of gemstone, exploring each one's unique beauty, rarity, and durability. It reveals how gems form, where they are found and mined, how to identify them, and more. With sumptuous color photos throughout, Gemstones offers dazzling insights into the world of the rare and the valuable."--